2022
DOI: 10.3390/nano12193327
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Electro-Oxidation on Catalysts with S-ZrO2-Decorated Graphene as Support in Fuel Cell Applications

Abstract: Direct ethanol fuel cells (DEFCs) are considered the most suitable direct alcohol fuel cell (DAFC) in terms of safety and current density. The obstacle to DEFC commercialization is the low reaction kinetics of ethanol (C2H5OH) oxidation because of the poor performance of the electrocatalyst. In this study, for the first time, graphene nanoplates (GNPs) were coated with sulfated zirconium dioxide (ZrO2) as adequate support for platinum (Pt) catalysts in DEFCs. A Pt/S-ZrO2-GNP electrocatalyst was prepared by a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…This indicates that the addition of zirconia through the adopted method does not introduce specific functional groups to the surface of the GNPs [61,62]. The FTIR results of GO and ZrO2-graphene nanoplates and sulfated zirconia-GNPs were presented in our previously published work [63]. 220), (200), and (111) diffraction peaks of the crystal surface, respectively, showing that it is a disordered Pt-Pd alloy.…”
Section: Structural Specifications Of Synthesized Support Materialsmentioning
confidence: 65%
See 2 more Smart Citations
“…This indicates that the addition of zirconia through the adopted method does not introduce specific functional groups to the surface of the GNPs [61,62]. The FTIR results of GO and ZrO2-graphene nanoplates and sulfated zirconia-GNPs were presented in our previously published work [63]. 220), (200), and (111) diffraction peaks of the crystal surface, respectively, showing that it is a disordered Pt-Pd alloy.…”
Section: Structural Specifications Of Synthesized Support Materialsmentioning
confidence: 65%
“…This reflection was chosen for the Scherrer examination due to its high-strength level. This formula can be defined as follows [70]: The FTIR results of GO and ZrO 2 -graphene nanoplates and sulfated zirconia-GNPs were presented in our previously published work [63].…”
Section: Structural Specifications Of Synthesized Support Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles are most widely used in medicine [ 23 , 24 ], spectroscopy [ 25 , 26 ], catalysis [ 27 , 28 ], and energy [ 29 , 30 ]. Catalysis and energy fields are of main interest in this paper, since the development of advanced catalysts based on metal nanoparticles with improved activity, selectivity and stability is an important and relevant task [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the authors demonstrated that it is possible to tailor and control the performance of graphene-based anodes in boron ion batteries by increasing the number of graphene layers, reaching cell voltage values that enable the practical use of these batteries, even as replacers of the more common Li ion ones. Yaldagard and co-workers [4] used coated graphene nanoplatelets as supporters for platinum electrocatalysts in direct ethanol fuel cells, and demonstrated the high activity of the Pt-coated graphene material for CO electrooxidation, its high catalytic activity for the EOR, and its lower charge transfer resistance in the presence of ethanol (i.e., enhanced ethanol oxidation activity), all essential aspects in this kind of fuel cell.…”
mentioning
confidence: 99%